Analysis of Factors Affecting Labor Productivity in the Convection Industry in Bima City: Analisis Faktor-Faktor Yang Mempengaruhi Produktivitas Tenaga Kerja Pada Industri Konveksi Di Kota Bima - Muhammad Dzahir; St. Maryam (Tinta Emas Publisher, 2023)
This study aims to analyze the effect of work experience, gender, wages, and age on labor productivity in the convection industry in the city of Bima. This type of research is descriptive quantitative. Tests were carried out on 78 respondents spread across five sub-districts in Bima City, namely, Asakota District, West Rasanae District, Mpunda District, Raba District, and East Rasanae District. The data used is primary data. With data collection techniques is documentation. The data analysis method uses multiple linear regression using the SPSS analysis tool. The results of the analysis show that the variables Work Experience, Gender, Wages, and Age simultaneously have a positive and significant effect on labor productivity in the convection industry in Bima City. Individually (partially), the variables of Work Experience and Wages in the convection industry in Bima City have a positive and significant effect on labor productivity, while the variables of gender and age have a negative and insignificant effect on labor productivity in the convection industry in Bima City.